Пленкообразующее вещество на основе нефтеполимерной смолы - Бондалетов В. Г. Владимир Григорьевич; Троян А. А. Анна Алексеевна; Бондалетова Л. И. Людмила Ивановна; Бондалетова А. В. Анна Владимировна
опубл. 10.02.15